2005
DOI: 10.1111/j.1365-2486.2005.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition increasingly dominates the responsiveness of juvenile beech and spruce to elevated CO2 and/or O3 concentrations throughout two subsequent growing seasons

Abstract: Saplings of Fagus sylvatica and Picea abies were grown in mono-and mixed cultures in a 2-year phytotron study under all four combinations of ambient and elevated ozone (O 3 ) and carbon dioxide (CO 2 ) concentrations. The hypotheses tested were (1) that the competitiveness of beech rather than spruce is negatively affected by the exposure to enhanced O 3 concentrations, (2) spruce benefits from the increase of resource availability (elevated CO 2 ) in the mixed culture and (3) that the responsiveness of plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 64 publications
(84 reference statements)
6
70
0
Order By: Relevance
“…However, the success of an individual plant generally depends on the ability to acquire resources from external pools (Kozovits et al 2005a). To ensure this, plant must allocate these resources into leaves and fine roots, which in turn are involved in the process of resource acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success of an individual plant generally depends on the ability to acquire resources from external pools (Kozovits et al 2005a). To ensure this, plant must allocate these resources into leaves and fine roots, which in turn are involved in the process of resource acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also suggest that the responsiveness of plants to N deposition, as observed for other atmospheric nutrients or pollutants (Kozovits et al 2005) depends in part on the type of competition (intra-or interspecific) occurring, and that this needs to be take into account in models of vegetation dynamics in response to nutrient deposition.…”
Section: Resultsmentioning
confidence: 87%
“…Phytotron studies to test O 3 effects on the competition between Fagus sylvatica and Picea abies revealed that the responses to O 3 strongly depended on the type of competition: although the response to O 3 of P. abies was not significantly affected by either intra-or interspecific competition, the competitive ability of this species was scarcely affected by O 3 as indicated by an enhanced aboveground growth of the competing F. sylvatica plants (Grams et al 2002;Kozovits et al 2005). Under conditions of interspecific competition, P. abies was found to be superior in nitrogen acquisition whereas F. sylvatica in turn appeared to be nitrogen-limited (Grams and Matyssek 2010;Kozovits et al 2005). Effects on nutrient efficiency indicate that processes of stress defence due to O 3 exposure trigger a nutrient demand at the expense of above-ground competition (Rodenkirchen et al 2009).…”
Section: Plant Competition and Community Compositionmentioning
confidence: 98%